Intercalated Iron Chalcogenides: Phase Separation Phenomena and Superconducting Properties - Krzton-Maziopa, Anna (Frontiers in chemistry, 2021)
Organic molecule-intercalated layered iron-based monochalcogenides are presently the subject of intense research studies due to the linkage of their fascinating magnetic and superconducting properties to the chemical nature of guests present in the structure. Iron chalcogenides have the ability to host various organic species (i.e., solvates of alkali metals and the selected Lewis bases or long-chain alkylammonium cations) between the weakly bound inorganic layers, which opens up the possibility for fine tuning the magnetic and electrical properties of the intercalated phases by controlling both the doping level and the type/shape and orientation of the organic molecules. In recent years, significant progress has been made in the field of intercalation chemistry, expanding the gallery of intercalated superconductors with new hybrid inorganic–organic phases characterized by transition temperatures to a superconducting state as high as 46 K. A typical synthetic approach involves the low-temperature intercalation of layered precursors in the presence of liquid amines, and other methods, such as electrochemical intercalation, intercalant or ion exchange, and direct solvothermal growths from anhydrous amine-based media, are also being developed. Large organic guests, while entering a layered structure on intercalation, push off the inorganic slabs and modify the geometry of their internal building blocks (edge-sharing iron chalcogenide tetrahedrons) through chemical pressure. The chemical nature and orientation of organic molecules between the inorganic layers play an important role in structural modification and may serve as a tool for the alteration of the superconducting properties. A variety of donor species well-matched with the selected alkali metals enables the adjustment of electron doping in a host structure offering a broad range of new materials with tunable electric and magnetic properties. In this review, the main aspects of intercalation chemistry are discussed, involving the influence of the chemical and electrochemical nature of intercalating species on the crystal structure and critical issues related to the superconducting properties of the hybrid inorganic–organic phases. Mutual relations between the host and organic guests lead to a specific ordering of molecular species between the host layers, and their effect on the electronic structure of the host will be also argued. A brief description of a critical assessment of the association of the most effective chemical and electrochemical methods, which lead to the preparation of nanosized/microsized powders and single crystals of molecularly intercalated phases, with the ease of preparation of phase pure materials, crystal sizes, and the morphology of final products is given together with a discussion of the stability of the intercalated materials connected with the volatility of organic solvents and a possible degradation of host materials.